Consumer response to price and income changes - O'Riordan, William K. (Statistical and Social Inquiry Society of Ireland, 1975)
The purpose of this paper is to show what can be learned about the reaction of Irish consumers to price and income changes by using the published time series data and the currently accepted models of consumer behaviour. Two difficulties present themselves immediately. First, the data are relatively scarce. At the time of writing, there are some twenty annual observations of consumer expenditure and, while there is a fairly fine division in the tables of current price expenditure (which provide 15 categories), the tables of constant price expenditure reduce this to eight. Secondly, there is at the moment no generally accepted "best" model of consumer behaviour. Many are available, and each has its strengths and weaknesses. The evidence suggests that overall, the Rotterdam model is best, but the margin of superiority is small. It would appear that reliable estimates of price elasticities cannot be obtained until more is known about the estimating characteristics of the demand models.
Read before the Society, 6 March 1975
Keywords: Consumer theory; Price elasticity; Income elasticity; Demand theory; 314.15